LCK and CD3E Orchestrate the Tumor Microenvironment and Promote Immunotherapy Response and Survival of Muscle-Invasive Bladder Cancer Patients - Zheng, Xiaonan; Liao, Xinyang; Nie, Ling; Lin, Tianhai; Xu, Hang; Yang, Lu; Shen, Bairong; Qiu, Shi; Ai, Jianzhong; Wei, Qiang (Frontiers in Cell and Developmental Biology, 2021)
Background: Studies have demonstrated the significance of multiple biomarkers for bladder cancer. Here we attempt to present biomarkers potentially predictive of the prognosis and immunotherapy response for muscle-invasive bladder cancer (MIBC). Method: Immune and stromal scores were calculated for MIBC patients from The Cancer Genome Atlas (TCGA). Core differential expression genes (DEGs) with prognostic value were identified and then validated through an independent dataset GSE31684. The clinical implications of prognostic genes and the inter-gene correlation were presented. The distribution of tumor-infiltrating immune cells (TICs), the correlation with tumor mutation burden (TMB) and the expression of eight immune-checkpoint-relevant genes and CD39 were accordingly compared. Two bladder cancer cohorts (GSE176307 and IMvigor210) receiving immunotherapy were collected to validate the prognostic value of LCK and CD3E for immunotherapy. Results: 361 MIBC samples from TCGA revealed a worse overall survival for higher stromal infiltration (P=0.009) but a better overall survival for higher immune infiltration (P=0.042). CD3E and LCK were independently validated by TCGA and GSE31684 to be prognostic for MIBC. CD3E was the most correlative gene of LCK with a coefficient of r=0.86 (P<0.001). CD8+ T cells and macrophage M1 are more abundant in favor of a higher expression of CD3E and LCK in MIBC and across pan-cancers. Immune checkpoints like CTLA4, CD274 (PD-1) and PDCD1 (PD-L1) were more expressed in CD3E-high and LCK-high groups for MIBC, and also for pan-cancers except for thymoma. LCK and CD3E had a moderate positive correlation with CD39 expression. Importantly, high-LCK and high-CD3E groups had higher percentage of responders than the low-expression groups both in GSE176307 (LCK: 22.73% vs 13.64%, CD3E: 22.00% vs 13.16%) and IMvigor210 cohorts (LCK: 28.19% vs 17.45%, CD3E: 25.50% vs 20.13%). Conclusion: CD3E and LCK were potential biomarkers of MIBC. CD3E and LCK were positively correlated with several regular immunotherapy biomarkers, which were supported by real-world outcomes from two immunotherapy cohorts.